Structural and energetic insight into the interactions between the benzolactam inhibitors and tumor marker HSP90α. (October 2015) - Guo, Xiao-Yan; Qi, Run-Peng; Xu, De-Gang; Liu, Xu-Hua; Yang, Xiao
Graphical abstract: Highlights: Computational methods were used to reveal the interactions of benzolactam inhibitors to HSP90α. Hydrophobic interactions contributed the most to the binding affinity. A good linear correlation was obtained between the calculated and the experimental binding free energies. Ala55, Ile96, and Leu107 are responsible for the different binding affinities of compounds. Abstract: The heat shock protein 90α (HSP90α) provides a promising molecular target for cancer therapy. A series of novel benzolactam inhibitors exhibited distinct inhibitory activity for HSP90α. However, the structural basis for the impact of distinct R1 substituent groups of nine benzolactam inhibitors on HSP90α binding affinities remains unknown. In this study, we carried out molecular docking, molecular dynamics (MD) simulations, and molecular mechanics and generalized Born/surface area (MM–GBSA) binding free energy calculations to address the differences. Molecular docking studies indicated that all nine compounds presented one conformation in the ATP-binding site of HSP90α N-terminal domain. MD simulations and subsequent MM–GBSA calculations revealed that the hydrophobic interactions between all compounds and HSP90α contributed the most to the binding affinity and a good linear correlation was obtained between the calculated and the experimental binding free energies ( R  = 0.88). The per residue decomposition revealed that the most remarkable differences of residue contributions were found in the residues Ala55, Ile96, and Leu107 defining a hydrophobic pocket for the R1 group, consistent with the analysis of binding modes. This study may be helpful for the future design of novel HSP90α inhibitors.